Atividade alelopática de extratos aquosos de Aristolochia esperanzae O. Ktze e Ocotea odorifera (Vell) Rohwer na germinação e crescimento de Lactuca sativa L. e Raphanus sativus L. - Gatti, Ana Beatriz (2003)
The objective of this work was analyze the effects of aqueous extracts of Aristolochia esperanzae organs in the germination and early growth of lettuce and radish. All the prepared extracts obeyed the ratio of 100g of plant material + 300 mL of distilled water to produce an extract 100% concentrated. This extract was diluted with distilled water to produce final concentrations of 75, 50 and 25%. In the germination tests the extracts of leaf, stem, root, fruit and flower, with concentration of 100, 75, 50, 25% were evaluated. In the seedlings growth, extracts of leaf, stem and root were used in the concentration of 100 and 50%. In the germination tests, four replicates of 30 seeds were distributed in Petri dishes with two filter paper moistened with 5 mL of the extracts, dried during 12 hours and moistened again with 4,5 mL of distilled water. In the first test, the rate and germination percentage was evaluated. In the growth test, the seeds were previously germinated (2-4mm root length) and transferred to plastic boxes containing the filter paper or coconut fiber, moistened with the extracts. The aerial part height, root length, dry mass and the presence of abnormalities in the seedlings were evaluated. Both tests were maintained at constant temperature (27ºC). The obtained results showed that the leaf extracts affected strongly the germination percentage and all the extracts, in different concentrations, delayed the germination of lettuce and radish seeds. In the growth test could be verified that the stem and root extracts caused abnormalities in the seedlings. The seedlings grown in filter paper presented bigger growth inhibition in relation to seedlings from coconut fiber. The extract concentration was the main responsible for the incentive or inhibition caused on lettuce and radish seedlings growth.